New records and taxonomic notes on Cryphalus Erichson, 1836 in Hawaiʻi (Coleoptera: Curculionidae: Scolytinae) - Johnson, Andrew J.; Honsberger, David; Beaver, Roger A. (Zootaxa, 2021)
We review the taxonomy and provide identification resources for the species of Cryphalus Erichson, 1836 from the Hawaiian Islands. Five species are present, Cryphalus brasiliensis (Schedl, 1976) new country record, Cryphalus mangiferae Stebbing, 1914, Cryphalus negrosensis Browne, 1979, Cryphalus sylvicola (Perkins, 1900), and Cryphalus trypanoides (Beeson, 1935) (= Cryphalus mollis Schedl, 1955 syn. nov.). Additionally, while reviewing the species, two species not present in Hawaiʻi are resurrected from synonymy with C. sylvicola: Cryphalus pini (Hopkins, 1915) stat. res. and Cryphalus swezeyi (Schedl, 1942) stat. res. None of the Hawaiian species are endemic, and most are known from most major Pacific islands, and presumed introduced. Cryphalus negrosensis is a likely recent introduction and is a frugivorous scolytine, collected from a wide range of fruits, and found breeding in Artocarpus altilis fruit pulp.